The Influence of Products, Prices, Location, Promotions, Store Atmosphere and Customer Service on Consumer Purchase Decisions: A Survey on Motor Power Consumers Soekarno Hatta Bandung Branch - Colly, Yoan; Lahindah, Laura (Devotion : Journal of Research and Community Service, 2024)
This study aims to analyze the effect of product, price, location, promotion, store atmosphere, and customer service on consumer purchasing decisions on electric motors at the Soekarno Hatta Bandung branch. The research method used is a survey with a quantitative approach. Data is collected through questionnaires distributed to consumers who have purchased electric motors at that location. Data analysis was carried out using multiple linear regression to test the effect of independent variables on purchasing decisions. The results showed that product, price, location, promotion, store atmosphere, and customer service have a significant influence on consumer purchasing decisions. The findings indicate that companies need to pay attention to these factors to improve purchasing decisions and customer satisfaction.